Chromatin state profiling reveals PRC2 inhibition as a therapeutic target in NRAS–mutant melanoma - Christopher J. Terranova (Molecular & Cellular Oncology, 2021)
Recently, we have generated 284 epigenomic maps in melanoma. Using chromatin state profiling we identify an association of NRAS-mutants with bivalent Histone H3 lysine 27 trimethylation (H3K27me3) and broad H3K4me3 domains. Reprogramming of bivalent H3K27me3 occurs on critical invasive-regulators and its resolution using Enhancer of Zeste Homolog 2 (EZH2) inhibition reduces invasive capacity and tumor burden in NRAS-mutant patient samples.